Plant community and climatic response to Miocene environmental change in the Pacific Northwest (USA): paleoecological tools and applications - Lowe, Alexander (My University, 2025)
The Miocene epoch (~23-5 Ma) offers important examples of past ecosystem response to global climatic changes in a relatively modern world and critical perspective to current and future climatic change, and as such, has been referred to as “the future of the past”. The Miocene is marked by two major climatic events: warming of the Miocene Climatic Optimum (MCO; 16.9-14.7 Ma) and cooling of the Middle Miocene Climatic Transition (MMCT; 14.7-13.8 Ma). The U.S. Pacific Northwest (PNW) offers a regional record of plant community and climatic response by hosting a suite of well-preserved fossil floras that span the MCO and MMCT in time. Although a rich history of work exists for these floras, an integrated paleoclimate and paleoecological study utilizing plant macrofossils, palynomorphs, and phytoliths, applying updated methodology, and constrained within a high-resolution radiometrically dated temporal framework is currently lacking. In addition, inferring plant ecological strategy, and its relationship to climate and disturbance, in these fossil plant records is hindered by limitations in current paleoecological tools. To refine the use of paleoecological tools, this dissertation presents two “modern analog” studies. In the first (Chapter 1), we refine the reconstruction of leaf economic spectrum (LES) strategies at the community- (i.e., site-) level through a global study of woody non-monocot angiosperm leaf mass per area (LMA) and its morphological correlate, the petiole metric (PM). We find LMA and PM correlate for community mean and variance, but not kurtosis, and provide the necessary equations to reconstruct these community-scale measures and associated uncertainty. This study also highlights the importance of increased temperature seasonality and decreased prevalence of evergreen species in driving low LMA and “fast” LES strategies in temperate climates. However, matching ‘absolute’ LMA distributions between fossil and modern sites does not allow reliable inference of analogous climate types. In the second modern analog study (Chapter 2), we test for links between leaf economic strategies and leaf morphology across succession in North Carolina. We find, among trees, “faster” leaf economic occur in early succession, as predicted, and highlight the utility of PM, leaf margin, and leaf morphological richness in interpreting successional dynamics and associated ecological strategies from fossil leaf assemblages sourced from temperate deciduous forests. The last study of this dissertation (Chapter 3) generates a record of plant communities and climate during the MCO and across the MMCT in the PNW. We find the MCO drove warmer-than-modern annual lowland temperatures, and precipitation like the wetter western PNW today but likely lacking summer drought, hosting mixed mesophytic closed canopy forests. Across the MMCT, the interior PNW cooled in annual and winter temperatures, and likely dried, but this climatic change was tempered closer to the coast. Plant community composition also changed across this interval, with a greater prevalence of deciduous species, and a considerable loss of exotic taxa (those no longer native to the US west coast) and a greater prevalence of open habitats in the PNW interior, which again, was tempered near the coast.
Thesis (Ph.D.)--University of Washington, 2024
Keywords: Paleobotany; Plant ecology; Paleoecology; Paleoclimate science; Plant sciences; Biology